Pandangan dosen hukum keluarga Islam UMM tentang aturan hak ikrar talak dalam kompilasi hukum Islam tinjauan feminist legal theory - Aini, Siti Nur (Maliki Interdisciplinary Journal, 2024)
The term "feminism" refers to the issue of equal rights between genders, especially women’s rights. In this contemporary era, more and more people are discussing and raising feminism issues through various platforms, including mass media, which openly and privately raise this issue. Feminism became more popular and more layers of society came to terms with this issue in different ways. Consequently, the aim of this research is to find out how the public responds to the issue of feminism in marriage, especially in terms of the rules regarding the right to vow divorce. This research uses empirical-qualitative methods. Empirical legal research is a type of research that places greater emphasis on observation or research in the field, which is a type of research that focuses on collecting empirical data in the field, namely by direct interviews with sources. Field analysis of each problem found is qualitative and comes from searches or research that produce descriptive data on individuals and their behavior. Based on the results of this research, it shows that the informants have almost the same understanding. Most of the informants took a Dominant Hegemony position in several sub-chapters or themes discussed; in other words, the majority of informants agreed or fully accepted the topic.